THE POTENTIAL OF VIRTUAL EXCURSIONS IN TEACHING RUSSIAN LANGUAGE - Babayeva Anjella Axatovna (Zeta Repository, 2023)
This article considers a virtual tour as a promising direction in teaching Russian as a foreign language. The objectives of this technology are the improvement of communicative competence, the formation of the worldview of students and the expansion of knowledge about the country, its history and culture. The novelty lies in the study of virtual excursions as an innovative educational tool that contributes to a deeper perception of educational material. Particular attention is paid to the fact that the use of the educational potential of a virtual tour in the Russian as a foreign language class helps to increase positive motivation to study the Russian language and Russian culture. It is concluded that the systematic introduction of educational virtual excursions into the educational process will enrich the methodology and allow building an effective educational environment.